Keefektifan Model Predict-Observe-Explain terhadap Kemampuan Pemahaman Konsep pada Mata Pelajaran IPA - Astuti, Marisa Rizqi; Sulianto, Joko; Purnamasari, Veryliana (Universitas Pendidikan Indonesia, 2017)
The background that encourages this research is comprehending the concept of fifth grade students in science subject very low. The objective to be achieved in this research is to know the differences in the ability of comprehending the concept of science in the fifth grade students of SDN 05 Telukwetan Jepara between learning using POE and learning model using conventional method. This research is an experimental research belongs to quantitative method. This research used True Experimental design. The type of the design is taken Posttest-Only Control Design. Based on the results of the research data analysis capabilities using the concept comprehension test two parties, obtained by tcount = 3.5259, and t_table = 2.0154 with a significance level of 5% by dk = n1 + n2 - 2 = 23 +23 - 2 = 44. Based on the results of the analysis, obtained tcount ttable is 3.5259 2.0154 then Ho rejected and Ha accepted. Thus, we can conclude that there are differences in the ability of science to the students' comprehending the concept of learning used POE and learning model using conventional method.